The Impact of Vaccination on COVID-19, Influenza, and Respiratory Syncytial Virus-Related Outcomes: A Narrative Review - Roberto Debbag; Deborah Rudin; Francesca Ceddia; John Watkins (Infectious Diseases and Therapy)
Abstract Vaccination represents a core preventive strategy for public health, with interrelated and multifaceted effects across health and socioeconomic domains. Beyond immediate disease prevention, immunization positively influences downstream health outcomes by mitigating complications of preexisting comorbidities and promoting healthy aging. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza virus, and respiratory syncytial virus (RSV) are common respiratory viruses responsible for broad societal cost and substantial morbidity and mortality, particularly among at-risk individuals, including older adults and people with frailty or certain comorbid conditions. In this narrative review, we summarize the overall impact of vaccination for these 3 viruses, focusing on mRNA vaccines, each of which exhibits unique patterns of infection, risk, and transmission dynamics, but collectively represent a target for preventive strategies. Vaccines for COVID-19 (caused by SARS-CoV-2) and influenza are effective against the most severe outcomes, such as hospitalization and death; these vaccines represent the most potent and cost-effective interventions for the protection of population and individual health against COVID-19 and influenza, particularly for older adults and those with comorbid conditions. Based on promising results of efficacy for the prevention of RSV-associated lower respiratory tract disease, the first RSV vaccines were approved in 2023. Immunization strategies should account for various factors leading to poor uptake, including vaccine hesitancy, socioeconomic barriers to access, cultural beliefs, and lack of knowledge of vaccines and disease states. Coadministration of vaccines and combination vaccines, such as multicomponent mRNA vaccines, offer potential advantages in logistics and delivery, thus improving uptake and reducing barriers to adoption of new vaccines. The success of the mRNA vaccine platform was powerfully demonstrated during the COVID-19 pandemic; these and other new approaches show promise as a means to overcome existing challenges in vaccine development and to sustain protection against viral changes over time. A graphical abstract and video abstract is available with this article. Graphic abstract